Harga, Citra Merek dan Kualitas Produk Terhadap Loyalitas Konsumen Sepatu Compass di Daerah Istimewa Yogyakarta - Ahsan Sumantika; Joko Priono (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
This study aims to determine the effect of price, brand image, and product quality on consumer loyalty for Compass shoes in the Special Region of Yogyakarta. The research was conducted in the Special Region of Yogyakarta. The sample in this study used 90 respondents and the technique used was probability sampling with purposive sampling method. The technique used in analyzing the data is multiple linear regression analysis, T test (partial), F test (tugether), the coefficient of determination (R2). The research shows the following results: Price has no effect on consumer loyalty with a sig value of 0.183 > 0.05; brand image has a significant influence on consumer loyalty with a sig value of 0.000 <0.05; product quality has a significant effect on consumer loyalty with a sig of 0.000 <0.05; and price, brand image, and product quality have an influence on consumer loyalty with a sig value of 0.000 <0.05. The magnitude of the influence or value of Adjusted R Square price, brand image, and product quality on consumer loyalty is 81.9%. This means that price, brand image, and product quality can explain consumer loyalty variables.